The smartphone in the context of the classroom in the primary school and in the higher education - Flores, Paula Quadros (2017)
Information and Communication Technologies (ICT) are implementing unique changes in the most diverse fields nowadays. The smartphone, in particular, because of its technological convergence characteristics and because it is a tool that everyone owns and carries with them, it is an added value for the school and for the student that owns a personalized mobile resource. However, the school is resistant to its inclusion in education and there are contradictory studies: some reveal perverse effects on education, but others show their potentialities [1-3]. This fact shows the importance of teacher training in the selection of a methodology that responds to the inclusion of this tool in education. How to use the smartphone in education? It is a challenge that we intend to answer by showing the potential of this emerging technology in the process of teaching and learning with children from 6 to 9 years of age (primary school) and with adults of higher education (engineering course). In this study, the use of smartphones was observed in three classrooms of the primary school, involving about 60 children, and in higher education classes, involving about 50 students. We used a qualitative approach, case study. Data were collected from direct observers of the educational practices in the different contexts. For data analysis, we used description and data interpretation. The results show that teachers adopt a socio-constructivist methodology centring the student in the learning process: (1) in the use of the tool (technical domain), (2) in the accomplishment of the task, (3) in the reflection and argumentation of the results obtained, (4) knowledge sharing, (5) behaviour management, attitudes, task leadership and (6) self-criticism. It is also verified that they use the smartphone as a resource to motivate the student, stimulate concentration on the task, facilitate the understanding of content, encourage participation in the activity and promote interaction and sharing with others. In addition, the use of smartphones generates emotions and develops cross curricular skills in education as well as facilitating access to information, stimulates the creation of creative engineering projects that have satisfied students not only for the novelty, but also for finding that a pocket tool can perform interesting monitoring and remote control tasks. Thus, the results show that smartphones have a high potential in education, as they can promote an opportunity for methodological recreation and modernization, offer research potential, the development of new educational equipment and tools, new ways of consolidating and evaluating curricular content, development of other expressive abilities in the academic, social and personal life of an individual, as well as develop autonomy and stimulate the satisfaction of the students by returning to education the motivation of the student. It is also a clever way of educating this new generation by finding other ways of learning to learn, learning to do and building knowledge, learning to be and being with others.